Comparative evaluation of calcium release of the apical plugs formed by mineral trioxide aggregate, Biodentine, and EndoSequence root repair material with and without 2% triple antibiotic powder: An in vitro study - Pooja Nitin Mapara; N D Shashikiran; Sachin Gugawad; Namrata Gaonkar; Savita Hadakar; Swapnil Taur; Dhanshri Khade (Wolters Kluwer Medknow Publications, 2020)
Background: Apical plug formation by mineral trioxide aggregate (MTA), Biodentine, and EndoSequence root repair material (RRM) is an excellent alternative technique to the conventional apexification procedure. Several antimicrobial agents have been incorporated in MTA and Biodentine to boost their antimicrobial efficacy. Considering the polymicrobial nature of root canal infection, a combination of potent antimicrobials like triple antibiotic powder (TAP) would be needed to address the diverse flora encountered. Calcium release is the consequential factor in the clinical excellence of these cements. Aim: The aim of the study was to evaluate and compare the calcium released from the apical plugs formed by MTA, Biodentine, and EndoSequence RRM with and without incorporation of 2% TAP. Methods: Ninety single-rooted teeth were divided into (n = 15) Group A: MTA + 2% TAP, Group B: MTA, Group C: Biodentine + 2% TAP, Group D: Biodentine, Group E: EndoSequence RRM + 2% TAP, and Group F: EndoSequence RRM to form the 4 mm apical plugs. Each sample tooth was then immersed in 10 ml of deionized water. Evaluation of calcium release was done on days 7, 15, and 30 using an atomic absorption spectrophotometer. Data were analyzed using one-way analysis of variance, post hoc test, and unpaired t-test. Results: Calcium released was maximum for Group E compared to Group F (P < 0.05), maximum for Group C compared to Group D, and was maximum for Group A compared to Group B (P < 0.05) at days 7, 15 and 30. Conclusion: Incorporation of 2% TAP resulted in increased calcium ions released from MTA, Biodentine, and EndoSequence RRM.